2020
DOI: 10.1159/000505934
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Efficacy of Retigabine and Flupirtine for Gout Arthritis Pain

Abstract: Introduction: Gout arthritis is an inflammatory disease characterized by severe acute pain. The goal of pharmacological gout arthritis treatments is to reduce pain, and thereby increase the patient's quality of life. The Kv7/M channel activators retigabine and flupirtine show analgesic efficacy in animal models of osteoarthritic pain. We hypothesized that these drugs may also alleviate gout arthritis pain. Objective: To determine the effects of retigabine and flupirtine on pain behavior associated with monosod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Retigabine and flupirtine have shown antinociceptive effects in a rat model of gout. It is believed that Kv7 channels generate low-threshold, inactivating voltage-gated potassium currents that play an important role in regulating the excitability of nociceptive neurons [ 225 ]. To date, the analgesic effect of RTG has been demonstrated in models of pain due to neuroplasticity, bone cancer [ 226 ], inflammation [ 227 ], nerve degeneration [ 228 ], and the application of capsaicin to the viscera [ 229 ].…”
Section: Mitochondrial Voltage-dependent Potassium Channelsmentioning
confidence: 99%
“…Retigabine and flupirtine have shown antinociceptive effects in a rat model of gout. It is believed that Kv7 channels generate low-threshold, inactivating voltage-gated potassium currents that play an important role in regulating the excitability of nociceptive neurons [ 225 ]. To date, the analgesic effect of RTG has been demonstrated in models of pain due to neuroplasticity, bone cancer [ 226 ], inflammation [ 227 ], nerve degeneration [ 228 ], and the application of capsaicin to the viscera [ 229 ].…”
Section: Mitochondrial Voltage-dependent Potassium Channelsmentioning
confidence: 99%
“…Therefore, MSU crystals were prepared and used to establish the GA rat model. The main clinical features of GA attack are inflammatory cell infiltration, joint swelling, severe pain and obvious hindered mobility of affected joints [1,4,7]. In the present study, we discovered that the paw volume and gait score were increased and the joint dysfunction was enhanced by MSU, which indicated that the MSU‐induced GA rat model was successfully established.…”
Section: Discussionmentioning
confidence: 50%
“…The onset of GA is triggered by the accumulation of excessive uric acid and MSU crystal formation in the joints and surrounding tissues [1,4]. Therefore, MSU crystals were prepared and used to establish the GA rat model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration-response curve from our MEA assay suggests that retigabine can achieve a 50% reduction of spontaneous firing with sub-micromolar concentrations. Prior studies that have assessed the effect of retigabine in pain models in many cases have assessed only a single dose or a small number of concentrations in the 1-10 µM range (Roza and Lopez-Garcia, 2008;Xu et al, 2010;Du et al, 2014;Hayashi et al, 2014;Abd-Elsayed et al, 2015;Li et al, 2019;Zhang et al, 2020). Taken together, this study and previous results implicate Kv7.2/ Kv7.3 channels as effective modulators of sensory neuron excitability and suggest that compounds that specifically target Kv7.2/Kv7.3 currents in sensory neurons, including human sensory neurons, might provide an effective approach toward pain relief.…”
Section: Figurementioning
confidence: 99%